Natural Killer Cell Receptors and Ligands Are Associated With Markers of HIV-1 Persistence in Chronically Infected ART Suppressed Patients - Ivison, Geoffrey T.; Vendrame, Elena; Martínez-Colón, Giovanny J.; Ranganath, Thanmayi; Vergara, Rosemary; Zhao, Nancy Q.; Martin, Maureen P.; Bendall, Sean C.; Carrington, Mary; Cyktor, Joshua C.; McMahon, Deborah K.; Eron, Joseph; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The latent HIV-1 reservoir represents a major barrier to achieving a long-term antiretroviral therapy (ART)-free remission or cure for HIV-1. Natural Killer (NK) cells are innate immune cells that play a critical role in controlling viral infections and have been shown to be involved in preventing HIV-1 infection and, in those who are infected, delaying time to progression to AIDS. However, their role in limiting HIV-1 persistence on long term ART is still uncharacterized. To identify associations between markers of HIV-1 persistence and the NK cell receptor-ligand repertoire, we used twin mass cytometry panels to characterize the peripheral blood NK receptor-ligand repertoire in individuals with long-term antiretroviral suppression enrolled in the AIDS Clinical Trial Group A5321 study. At the time of testing, participants had been on ART for a median of 7 years, with virological suppression <50 copies/mL since at most 48 weeks on ART. We found that the NK cell receptor and ligand repertoires did not change across three longitudinal samples over one year—a median of 25 weeks and 50 weeks after the initial sampling. To determine the features of the receptor-ligand repertoire that associate with markers of HIV-1 persistence, we performed a LASSO normalized regression. This analysis revealed that the NK cell ligands CD58, HLA-B, and CRACC, as well as the killer cell immunoglobulin-like receptors (KIRs) KIR2DL1, KIR2DL3, and KIR2DS4 were robustly predictive of markers of HIV-1 persistence, as measured by total HIV-1 cell-associated DNA, HIV-1 cell-associated RNA, and single copy HIV-RNA assays. To characterize the roles of cell populations defined by multiple markers, we augmented the LASSO analysis with FlowSOM clustering. This analysis found that a less mature NK cell phenotype (CD16+CD56dimCD57-LILRB1-NKG2C-) was associated with lower HIV-1 cell associated DNA. Finally, we found that surface expression of HLA-Bw6 measured by CyTOF was associated with lower HIV-1 persistence. Genetic analysis revealed that this was driven by lower HIV-1 persistence in HLA-Bw4/6 heterozygotes. These findings suggest that there may be a role for NK cells in controlling HIV-1 persistence in individuals on long-term ART, which must be corroborated by future studies.